Sustainable nature-based tourism development: A feasibility assessment of a coastal tourism area - Anugrah Sahri Syawal; La Ode Midi; La Ode Muhammad Erif; La Gandri (Ecotourism and Environment Conservation, 2025)
Baground: Coastal tourism areas should be developed with an environmentally sound approach to achieving sustainable tourism, which safeguards the environment while providing a decent livelihood for surrounding communities. This study aims to assess the feasibility level of Taipa Beach tourism in Taipa Village, Lembo District, North Konawe Regency. Unlike previous studies that focus primarily on promotion or visitor statistics, this research applies a comprehensive feasibility framework, offering broader insights into sustainable coastal tourism development. Methods: Fieldwork was conducted from September to November 2024, applying the Guidelines for Analyzing the Area of Operation of Natural Tourism Objects and Attractions (ADO-ODTWA) issued by the Director General of PHKA (2003). Findings: The results show that Taipa Beach is feasible as an alternative natural tourism area, with an overall feasibility index value of 81.6%. Of the eight criteria assessed, six were declared feasible (attractiveness, accessibility, facilities and infrastructure, security, conditions around the area, and relationships with other tourist attractions), while two criteria were not yet feasible (climate and accommodation). Strategic interventions are therefore required to improve accommodation facilities and develop adaptation measures for non-ideal climatic conditions, such as supporting infrastructure to manage extreme weather. Conclusion:  Overall, Taipa Beach is considered feasible for sustainable nature-based tourism development, with a high feasibility index of 81.6%. However, improvements in accommodation facilities and climate adaptation measures are essential to enhance its sustainability and resilience as an eco-tourism destination in North Konawe Regency. Novelty/Originality of this Article: This study contributes not only to local tourism planning but also to the broader discourse on sustainable tourism and ecotourism feasibility. By integrating multi-dimensional criteria into the feasibility assessment, the research provides a replicable model for coastal tourism development in other regions facing similar challenges.